Characterization of lean patients with nonalcoholic fatty liver disease: potential role of high hemoglobin levels - YILMAZ, YUSUF (TAYLOR & FRANCIS LTD, 2015)
Objective. Overweight and obesity are major risk factors for the development of nonalcoholic fatty liver disease (NAFLD). However, a minority of NAFLD patients have a body mass index (BMI) < 25 kg/m(2) (lean NAFLD). We sought to investigate whether significant differences exist between lean NAFLD and more common forms of NAFLD associated with overweight/obesity. Patients and methods. A total of 483 consecutive patients with biopsy-proven NAFLD were enrolled. Lean NAFLD was defined as having a BMI < 25 kg/m(2). We identified 37 patients with lean NAFLD (7.6%). Results. Compared with NAFLD patients with overweight/obesity, lean NAFLD patients were younger, had lower blood pressure values, higher levels of hemoglobin, a lower prevalence of the metabolic syndrome, and less severe hepatic fibrosis. In NAFLD patients with overweight/obesity, diabetes was the only independent predictor of nonalcoholic steatohepatitis (NASH). In lean NAFLD, the only variable independently associated with NASH was hemoglobin. Alanine aminotransferase and diabetes were independent predictors of fibrosis >= 2 in NAFLD patients with overweight/obesity, whereas hemoglobin was the only independent predictor of fibrosis >= 2 in lean NAFLD. Conclusion. In summary, lean NAFLD patients are younger and show less severe hepatic fibrosis. However, such subjects have higher hemoglobin levels, which seem to predict the histological severity.
Keywords: body mass index; fibrosis; hemoglobin; nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; NAFLD; PREVALENCE; PHLEBOTOMY; DIAGNOSIS